Effect of abscisic acid on rice defense mechanism against Fusarium oxysporum - Peng, Guo; Xiu, Yang Ming; Peng, Li Yun; Younis, Haseeb; Zhe, Ni; Feng, Xu Xiao; Ran, Liu Qing; Liang, Xiong Tian; Hua, Zhang Jun (Journal of Phytology, 2024)
Fusarium oxysporum is one of the most destructive pathogens which causes rice seedling blight. ABA is part of a large signaling system that provides an effective system against microbial and environmental manipulations. The role of ABA in plant defense mechanisms is not clear. In this experiment, we prove the role of abscisic acid (ABA) in boosting rice plant resistance against F. oxysporum and optimizing ABA concentrations against F. oxysporum. This study is divided into two experiments. In the first experiment, we used various ABA concentrations of 0.0, 0.05, 0.1, 0.2, and 0.25 mmol/L under F. oxysporum stress. In the second experiment, we use Fluridone FLD as an ABA inhibitor with the following treatments, (F) is only applied with F. oxysporum (ABA+F), abscisic acid with F. oxysporum (ABAI+F), ABA inhibitor Fluridone with F. oxysporum (ABAI), where only ABA inhibitor Fluridone was applied and CK was used as a control. The results revealed that all the plants treated with ABA exhibit better performance against F. oxysporum, except those treated without ABA. ABA concentrations of 0.2 mmol/L effectively decreased the disease index and disease incidence rate as well as improved the quality of seedlings. ABA effectively increased the activity of defense-related enzymes like PPO, POD, PAL and SOD. ABA also lowers down the MDA content which proves its effectiveness against F. oxysporum. ABA resistance was also proved by plants treated with the abscisic acid inhibitor ABAI (Fluridone FLD). The ABA inhibitor reduced the rice resistance to F. oxysporum, by conforming the expression of defense-related genes PRB1-3, PRBI-2 and Xa39(t). These gene expressions indicate the involvement of ABA in plant defense system.